Análisis de las estrategias de marketing publicitario en la Cooperativa de Ahorro y Crédito San Antonio del Cantón Montalvo - Pazmiño Figueroa, Leidy Viviana (2020)
This research raises the study of advertising marketing strategies “San Antonio” savings and credit cooperative, Montalvo’s matrix. This locality being one of the cantons that belongs to the province of Los Ríos, the investigation sub line to which belongs The research includes marketing and commercialization, because it analyzes how the strategies influence the commercial area of said institution, the banks and the savings and credit cooperatives in Ecuador over the last five years have decided to reinvent themselves in order to reach a greater number of customers, through the application of modern marketing trends inasmuch as more than 50% of the customer segment comprises millennials who use modern virtual means to learn about the products and services that entities offer, leaving behind the old marketing practices; and influencing your decision to purchase or affiliate with the entity.